INFLUENCE OF SAVING AND ECONOMIC GROWTH ON INVESTMENT IN INDONESIA THE PERIOD OF 1990-2019 - Hijri Juliansyah; Suprianti Suprianti; Fanny Nailufar (LPPM Universitas Malikussaleh, 2021)
This study aims to analyze the effect of savings and economic growth on investment in Indonesia from 1990 to 2019. The data used in this study are secondary data for the period 1990 - 2019. This research uses the VECM (Vector Error Correction Model) for analyzing the data. The unit root test is carried out with the Augmented dickey fuller (ADF) test where all the variables are stationary on the second different. The results showed that, in short run and in the long run, saving have no effect on investment in Indonesia, meanwhile in the short run economic growth has no effect investment, but in long run economic growth has a positive and significant effect on the invesmant in Indonesia.